Interactome Analysis of the Influenza A Virus Transcription/Replication Machinery Identifies Protein Phosphatase 6 as a Cellular Factor Required for Efficient Virus Replication - York, Ashley (J Virol, 2014)
The negative-sense RNA genome of influenza A virus is transcribed and replicated by the viral RNA-dependent RNA polymerase (RdRP). The viral RdRP is an important host range determinant, indicating that its function is affected by interactions with cellular factors. However, the identities and the roles of most of these factors remain unknown. Here, we employed affinity purification followed by mass spectrometry to identify cellular proteins that interact with the influenza A virus RdRP in infected human cells. We purified RdRPs using a recombinant influenza virus in which the PB2 subunit of the RdRP is fused to a Strep-tag. When this tagged subunit was purified from infected cells, copurifying proteins included the other RdRP subunits (PB1 and PA) and the viral nucleoprotein and neuraminidase, as well as 171 cellular proteins. Label-free quantitative mass spectrometry revealed that the most abundant of these host proteins were chaperones, cytoskeletal proteins, importins, proteins involved in ubiquitination, kinases and phosphatases, and mitochondrial and ribosomal proteins. Among the phosphatases, we identified three subunits of the cellular serine/threonine protein phosphatase 6 (PP6), including the catalytic subunit PPP6C and regulatory subunits PPP6R1 and PPP6R3. PP6 was found to interact directly with the PB1 and PB2 subunits of the viral RdRP, and small interfering RNA (siRNA)-mediated knockdown of the catalytic subunit of PP6 in infected cells resulted in the reduction of viral RNA accumulation and the attenuation of virus growth. These results suggest that PP6 interacts with and positively regulates the activity of the influenza virus RdRP. IMPORTANCE Influenza A viruses are serious clinical and veterinary pathogens, causing substantial health and economic impacts. In addition to annual seasonal epidemics, occasional global pandemics occur when viral strains adapt to humans from other species. To replicate efficiently and cause disease, influenza viruses must interact with a large number of host factors. The reliance of the viral RNA-dependent RNA polymerase (RdRP) on host factors makes it a major host range determinant. This study describes and quantifies host proteins that interact, directly or indirectly, with a subunit of the RdRP. It increases our understanding of the role of host proteins in viral replication and identifies a large number of potential barriers to pandemic emergence. Identifying host factors allows their importance for viral replication to be tested. Here, we demonstrate a role for the cellular phosphatase PP6 in promoting viral replication, contributing to our emerging knowledge of regulatory phosphorylation in influenza virus biology.